2022
DOI: 10.1002/advs.202202145
|View full text |Cite
|
Sign up to set email alerts
|

3D Tomographic Analysis of the Order‐Disorder Interplay in the Pachyrhynchus congestus mirabilis Weevil

Abstract: The bright colors of Pachyrhynchus weevils originate from complex dielectric nanostructures within their elytral scales. In contrast to previous work exhibiting highly ordered single‐network diamond‐type photonic crystals, here, it is shown by combining optical microscopy and spectroscopy measurements with 3D focused ion beam (FIB) tomography that the blue scales of P. congestus mirabilis differ from that of an ordered diamond structure. Through the use of FIB tomography on elytral scales filled with platinum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…While the used procedure can approximate the ff , accurate 3D tomographic data for ordered and quasi‐ordered scales of P. congestus mirabilis weevils exhibited ff values of 0.44 and 0.32, respectively. [ 20 ] The study of other Pachyrhynchus specimens with ordered PCs reported ff ‐values of 0.4, but since they were also based on 2D data, these values are only estimates. [ 29,30 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…While the used procedure can approximate the ff , accurate 3D tomographic data for ordered and quasi‐ordered scales of P. congestus mirabilis weevils exhibited ff values of 0.44 and 0.32, respectively. [ 20 ] The study of other Pachyrhynchus specimens with ordered PCs reported ff ‐values of 0.4, but since they were also based on 2D data, these values are only estimates. [ 29,30 ]…”
Section: Resultsmentioning
confidence: 99%
“…Pachyrhynchus weevils are an ideal species to study variations in structural coloration, not only because of their vast color palette extending from deep‐red to the UV, but also because of their ability to create both ordered and quasi‐ordered 3D PCs. [ 20 ] Although ordered and quasi‐ordered 3D PCs within a single specimen have previously been reported, [ 21,22 ] ) these ordered and quasi‐ordered scales were differently colored and located in distinct sections of the elytron. Furthermore, these previously investigated species lack the vast range in colors found across Pachyrhynchus .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations